Not all quad bikers are the same: unsupervised cluster analysis identifying injury risk groups among quad bike riders in Dubai, UAE - Michal Grivna; Ahmed Mohammed; Preetha Menon; Saeeda Buti Saeed; Ibrahim Abdalla Alfaki; Mohamed El Sadig; Omar Ahmed Zain Alsakaf; Rashad Gamar (BMJ Public Health, 2025)
Objective Quad bike riders in Dubai (UAE) constitute a highly diverse group with varying driving skills and familiarity with the desert environment. In the absence of evidence on the quad bike riders in the region, we attempted to describe the most vulnerable risk groups using routinely collected injury data. This may hopefully inform the most effective injury prevention strategies for the region.Methods Four-year injury incident reports of 226 patients rescued by Dubai ambulance were grouped into three clusters using two-step cluster analysis in SPSS.Result The three clusters that emerged were ‘Older Tourist-Expatriates’ (n=86), ‘Prompt Young Emiratis’ (n=76) and ‘Tightlipped Young Colliders’ (n=60). Older tourists were more likely to ride during the daytime and sustained milder injuries due to rollover. Prompt Young Emirati riders who experienced severe head, neck and spine injuries from nighttime rollovers were more likely to call for an ambulance without delay. Tightlipped Young Colliders were very young riders who experienced quad bike collisions or did not report their crash history. One in five riders in Clusters 1 and 3 delayed calling the ambulance by more than 6 hours.Conclusion Young nationals with severe injuries due to night collisions and rollovers during winter would benefit from increased guardianship, vehicle modification and crowd control interventions. In addition, emergency first aid services for tourists and nationals should be allocated to the major quad biking desert locations in Dubai to relieve the burden on emergency ambulatory care services.